2013
DOI: 10.1111/jfb.12137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sampling techniques on population assessment of invasive round goby Neogobiusmelanostomus

Abstract: In this study, a comparison of point abundance sampling (PAS) electrofishing, angling with two different hook sizes and trap-based fishing was performed in a non-wadeable river to analyse their effects on catch per unit effort (CPUE) and population characteristics of invasive round goby Neogobius melanostomus. PAS electrofishing was identified as the most effective (mean ± s.e. CPUE = 57 ± 4 N. melanostomus min(-1) ) and least selective method in terms of size, feeding status and species composition. Angling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 45 publications
0
33
1
Order By: Relevance
“…In line with our findings, Gutowsky and Fox (2011) [8] also caught the largest individuals of each sex at initially invaded areas, but found significantly larger males than females at the edges of upstream expansion areas. This size-specific difference may result from using angling as a sampling method by these authors since angling was found to be selective for larger males [65]. In contrast to our findings, Brownscombe and Fox (2012) [16] caught smaller round gobies at recently invaded areas compared to longer established sites, indicating that local habitat conditions and community structure can strongly influence trait selection.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In line with our findings, Gutowsky and Fox (2011) [8] also caught the largest individuals of each sex at initially invaded areas, but found significantly larger males than females at the edges of upstream expansion areas. This size-specific difference may result from using angling as a sampling method by these authors since angling was found to be selective for larger males [65]. In contrast to our findings, Brownscombe and Fox (2012) [16] caught smaller round gobies at recently invaded areas compared to longer established sites, indicating that local habitat conditions and community structure can strongly influence trait selection.…”
Section: Discussioncontrasting
confidence: 93%
“…This observation is in line with this study, as four out of five first recorded invaders in autumn 2010 (right shoreline) and seven out of thirteen pioneers in autumn 2011 (right shoreline) were female at the IF2010, suggesting that a higher proportion of females may contribute to range expansion in round goby. Despite the sex-selectivity of the different sampling techniques used, which is higher in hook-and-line based sampling than in electrofishing as applied in this study (see Brandner et al, 2013 [65]), migrating adult females appear to be a main driver of range expansion. Among various reasons, inbreeding depression avoidance, asymmetry in the costs of dispersal and mating system characteristics [75] can cause sex-biased dispersal in invasions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The number of available nests and the sex ratio are both important factors affecting reproduction because of round goby's nest guarding strategy (Meunier et al., ). A challenging issue is that the observed sex ratio can be biased by the catch technique (Brandner, Pander, Mueller, Cerwenka, & Geist, ; Thompson & Simon, ) and by invasion stage. Because of a lack of own field data and unclear literature values (N'Guyen et al., ), in our model we assumed equal proportions of removed males and females (Figure in Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…The variety of collection methods used to sample N . melanostomus may introduce gear bias as an analysis covariate (Brandner et al , ). Kick seining has been demonstrated to be useful in wadeable shoreline habitats (Jude et al , ), while bottom trawling has been effective for non‐wadeable areas (Clapp et al , ).…”
Section: Discussionmentioning
confidence: 99%